Media framing and public perception: a content analysis of the Nation and ThisDay newspapers' coverage of the 2023 presidential elections in Nigeria - Ogundare, Olukayode Kay, author; Kodrich, Kris, advisor; Wolfgang, David, committee member; McIvor, David, committee member (Colorado State University. Libraries, 2025)
This thesis explores the role of prominent Nigerian newspapers, The Nation and ThisDay, in helping to shape public perception of the 2023 presidential elections in Nigeria. With framing theory as a framework, the study conducts a detailed content analysis to examine how these newspapers portrayed political candidates, issues, and events during the election campaign. Analyzing each newspaper's thematic and episodic frames, the research uncovers noticeable patterns in media framing strategies and discusses how they may impact public perception and understanding of the electoral process. This study contributes to the broader understanding of media influence on political communication in Nigeria and highlights how newspapers may shape public opinion during critical democratic events.
Keywords: democracy in Nigeria; Nigeria; Nigerian media; media framing; content analysis; Nigeria elections 2023